“Raise as if we were not working and work as if we were not having children” reflections on the labor integration of migrant mothers raising in Chile - Castillo, Lucia Odette (Población y Salud en Mesoamérica, 2023)
The childrearing practices deployed by migrant mothers are influenced by the precariousness of their subsistence spaces, as well as the mothers´ knowledge and experiences. From the theoretical assumptions of intersectionality that reveals the imbricated networks based on gender, ethnicity-race and class that establish relations of inequality between social superstructures and mothers-migrants, it is proposed to respond to the general objective of analyzing the influence of precariousness work of migrant mothers in raising their sons and daughters in Chile. From a Latin American perspective, it is hoped to open the discussion regarding a local phenomenon as a manifestation of situated knowledge and, in turn, make visible the discrimination, subordination and submission of migrant women mothers, which explains the general dismissal of their vulnerable integration into the country and in which the upbringing of their sons and daughters take place. Through a qualitative methodology based on symbolic interactionism, 39 semi-structured interviews were conducted with Venezuelan, Peruvian and Haitian migrant mothers, which were subjected to thematic analysis and theorized according to the defined research objectives. As a result, it is obtained that migrant mothers tend to access precarious and informal jobs against which they deploy different strategies that range from job abandonment, renouncing their maternity rights, acceptance of double presence and the formation of chains. care packages to make the childrearing compatible with work. The conclusions show that the labor integration of migrant mothers in Chile outlines the practices of childrearing from a permanent negotiation between subsistence, the maintenance of ties and their cultural heritage, where the dimensions of gender, race and class outline the intensity of these transactions that make manifest the social location of subalternity of migrant mothers, and that is intensified in the case of Haitian mothers since the greater representation of otherness is embodied in them.